Lunch with Buddha : [a novel] - Merullo, Roland (AJAR Contemporaries, 2012)
Otto Ringling and his sister Cecelia could not be more different. He's just turned 50, an editor of food books at a prestigious New York publishing house, a man with a nice home in the suburbs, children he adores, and a sense of himself as being a mainstream, upper-middle-class American. Cecelia is the last thing from mainstream. For two decades she's made a living reading palms and performing past-life regressions. She believes firmly in our ability to communicate with those who have passed on. It will turn out, though, that they have more in common than just their North Dakota roots.